TEACHING AT THE RIGHT LEVEL: ADAPTIVE INSTRUCTION AND STUDENT ENGAGEMENT IN SECONDARY EDUCATION - Zaizafun Sintarana; Deny Hadi Siswanto; Kintoko Kintoko (Penelitian dan Pengembangan Ilmu, 2026)
This study aims to examine the implementation of the Teaching at the Right Level (TaRL) approach at SMA Muhammadiyah Mlati and its influence on the learning process and student participation. The study employed a qualitative descriptive research design. Data were collected through classroom observations, semi-structured interviews with teachers and students, and documentation analysis. Observations focused on how teachers implemented diagnostic assessments, ability-based grouping, and differentiated instructional strategies during the learning process. Interviews were conducted to gain deeper insights into the experiences and perceptions of teachers and students regarding the implementation of TaRL. In addition, supporting documents such as diagnostic assessment results, lesson plans, learning modules, worksheets, and formative assessment records were analyzed to strengthen the research findings. The collected data were analyzed using an interactive qualitative analysis model consisting of data reduction, data display, and conclusion drawing. The results show that the implementation of TaRL begins with mapping students’ initial abilities through diagnostic assessments, followed by grouping students based on their learning levels and adjusting instructional strategies according to students’ needs. These practices contribute to increased student participation, confidence, and conceptual understanding, thereby improving the effectiveness of the learning process.